A thiolate-bridged ruthenium–molybdenum complex featuring terminal nitrido and bridging amido ligands derived from the N–H and N–N bond cleavage of hydrazine. Issue 29 (5th July 2022) - Li, Yahui; Su, Linan; Yang, Dawei; Di, Kai; Wang, Baomin; Qu, Jingping
Abstract : A structurally well-characterized thiolate-bridged RuMo complex featuring terminal nitrido and bridging amido ligands was obtained by the N–N and N–H bond cleavage of hydrazine. Abstract : Biomimetic di- or multimetallic complexes featuring N x H y species in a sulfur-rich coordination sphere have attracted considerable attention in modelling the possible scenarios of biological nitrogen fixation by nitrogenases. Although the active site of nitrogenases is a complex heterometallic sulfur cluster, the feasibility of N x H y species on different metal sites is scarcely investigated. Herein, we report an unprecedented thiolate-bridged ruthenium–molybdenum complex featuring bridging amido and terminal nitrido ligands obtained by cleaving the N–N and N–H bonds of hydrazine. Remarkably, this RuMo complex is also capable of catalyzing the reduction of hydrazine to ammonia. Overall, this rare activation pattern of hydrazine on a thiolate-bridged RuMo platform provides new insight into the heterometallic cooperativity in nitrogenase.